Feasibility study for a development of a mechanical agricul tural cutter using pressurized air flow - Nurul Afrah Diniah Mohammad Nadzim (School of Manufacturing Engineering, University Malaysia Perlis, 2016)
The aim of this study is to solve the problem of the use of rechargeable batteries for the smart harvester cutter. Besides, to analyze the mechanisms employed to study the existing batteries and defects that occur during the use of rechargeable batteries for the cutter. Based on the results, The design for new cutter usign of air blower 'Smart Harver' is created. In addition, the modification for exising cutter was done to improve performance of smart harvester cutter.